Oral administration of probiotic bacteria (E. coli Nissle, E. coli O83, Lactobacillus casei) influences the severity of dextran sodium sulfate-induced colitis in BALB/c mice - Kokesová, A; Frolová, L; Kverka, M; Sokol, D; Rossmann, P; Bártová, J; Tlaskalová-Hogenová, H (Folia microbiologica, 2006)
Our study examined whether repeated preventive oral administration of live probiotic bacterial strains Escherichia coli O83:K24:H31 (Ec O83), Escherichia coli Nissle 1917 O6:K5:H1 (Ec Nis) and Lactobacillus casei DN 114001 (Lc) can protect mice against dextran sodium sulfate (DSS)-induced colitis. A significant decrease in average symptom score was observed in Ec O83-, Ec Nis- and Lc-pretreated group (p < 0.05). Significant differences in body mass loss between Lc pretreated mice with DSS-induced colitis were found when compared with nontreated mice (p < 0.05). PBS pretreated mice had a significantly shorter colon than Ec O83-, Ec Nis- and Lc-pretreated mice (p < 0.05). Administration of Lc significantly decreased the severity of DSS induced histological marks of inflammation (p < 0.05). A significant difference (p < 0.05) was also found in specific IgA level against given probiotic in enteral fluid between colitic mice and healthy mice pretreated with Ec 083 and Ec Nis.
Keywords: Lacticaseibacillus casei; kolon; Colitis, Ulcerative; ulcerózní kolitida; Dextran Sulfate; střevní sliznice; Escherichia coli; myši inbrední BALB C; Administration, Oral; Colon; zvířata; Immunoglobulin A; myši; Mice; Histocytochemistry; síran dextranu; Lactobacillus casei; imunoglobulin A; probiotika; Animals; aplikace orální; histocytochemie; Disease Models, Animal; Intestinal Mucosa; Probiotics; Mice, Inbred BALB C; modely nemocí na zvířatech